Perbedaan Mual dan Muntah Ibu Hamil Trimester I yang Diberikan Ekstrak Jahe dan Ekstrak Daun Mint - Anita Anita; Aprina Aprina; Ratna Aryani (Jurnal Kesehatan, 2018)
Study of literature with meta-analysis was obtained 7 out of 10 women around the world to experience nausea and vomiting during pregnancy, with an average incidence of 69.4% (66.5-72.3%, CI 95%). The purpose of research to find out the difference of nausea and vomiting of pregnant women through assessment scale Rhodes after administration of ginger extract and mint leaf extract in Inpatient Health Center Bandar Lampung in 2016. The target of research is the discovery of alternative therapy/food in the community to reduce nausea and vomiting of pregnant women. Type of research is quantitative research, design experimental research. The study population is the entire first-trimester pregnant women who visit health centers Inpatient Bandar Lampung, with 10 (ten) PHC hospitalization. The total sample was 102, the group treated with the extract of ginger were 34 respondents, a group treated extract of mint leaves were 34 respondents, and the group without treatment who received standard procedures health centers (Vitamin B6) were 34 respondents, with the criteria of pregnant women the first trimester without GI disease. The results of the study there were significant differences between the measurement value of nausea and vomiting before and after administration of ginger extract, extract of mint and a control group with p = 0.001 in the extract of ginger, p=0.000 in the extract mint, and p=0.001 in the control group with (standard treatment of health centers with vitamin B6). There were no differences between mean nausea and vomiting in the first trimester pregnant women who received ginger extract and mint with a p=0.548, ginger extract and control groups with p=0.807, mint extract and control groups with p=0,407 ginger and mint can be an alternative therapy to reduce vomiting and nausea of pregnant woman in trimester I. Advanced research about the composition, dosage and side effects of ginger and mint benefit to the problem of gastrointestinal disorders who experience nausea and vomiting.